Enterococcus faecalis Glycolipids Modulate Lipoprotein-Content of the Bacterial Cell Membrane and Host Immune Response. - Christian Theilacker; Ann-Kristin Diederich; Andreas Otto; Irina G Sava; Dominique Wobser; Yinyin Bao; Katrin Hese; Melanie Broszat; Philipp Henneke; Dörte Becher; Johannes Huebner (PLoS ONE, 2015)
In this study, we investigated the impact of the cell membrane composition of E. faecalis on its recognition by the host immune system. To this end, we employed an E. faecalis deletion mutant (ΔbgsA) that does not synthesize the major cell membrane glycolipid diglycosyl-diacylglycerol (DGlcDAG). Proteomic analysis revealed that 13 of a total of 21 upregulated surface-associated proteins of E. faecalis ΔbgsA were lipoproteins. This led to a total lipoprotein content in the cell membrane of 35.8% in ΔbgsA compared to only 9.4% in wild-type bacteria. Increased lipoprotein content strongly affected the recognition of ΔbgsA by mouse macrophages in vitro with an increased stimulation of TNF-α production by heat-fixed bacteria and secreted antigens. Inactivation of the prolipoprotein diacylglycerol transferase (lgt) in ΔbgsA abrogated TNF-α induction by a ΔbgsA_lgt double mutant indicating that lipoproteins mediate increased activation of mouse macrophages by ΔbgsA. Heat-fixed ΔbgsA bacteria, culture supernatant, or cell membrane lipid extract activated transfected HEK cells in a TLR2-dependent fashion; the same was not true of wild-type bacteria. In mice infected intraperitoneally with a sublethal dose of E. faecalis we observed a 70% greater mortality in mice infected with ΔbgsA compared with wild-type-infected mice. Increased mortality due to ΔbgsA infection was associated with elevated plasma levels of the inflammatory cytokines TNF-α, IL-6 and MIP-2. In summary, our results provide evidence that an E. faecalis mutant lacking its major bilayer forming glycolipid DGlcDAG upregulates lipoprotein expression leading to increased activation of the host innate immune system and virulence in vivo.